Marsialapari As A Tradition of Mutual Cooperation in Relationship with National Characters for The Anglola Mandailing Community - Ahmad Laut Hasibuan; Nurhayati Harahap; Amrin Saragih; Asnawi Asnawi; Bincar Nasution (International Journal of Educational Research Excellence (IJERE), 2024)
ABSTRACTThe local wisdom of marsialapari, a mutual assistance activity in the Angkola Mandailing community, represents a form of local wisdom that remains prevalent today. This study aims to examine the values embedded in the local wisdom of marsialapari and its relevance to character education for the Angkola Mandailing community. The research employs a research and development method. The findings reveal that marsialapari as local wisdom is a mutual assistance activity that characterizes the Angkola Mandailing community as an expression of the philosophy of holong (compassion) and domu (togetherness) within the framework of local wisdom encapsulated in dalihan na tolu. The tradition of marsialapari in the Angkola Mandailing community is closely linked to the development of national character in Indonesia, which is founded on noble principles such as solidarity, the spirit of mutual cooperation, ethics, religiosity, and respect for diversity. These principles have the potential to create a generation that is moral, high-integrity, and of high quality, a tradition that remains well-maintained and practiced to this day. Keywords: Marsiadapari, Mutual Cooperation, Angkola Mandailing, Local wisdom, National character,